A Breakdown of Imagined Visuomotor Transformations and Its Neural Correlates in Young Elderly Subjects. (15th December 2018) - Zapparoli, Laura; Gandola, Martina; Banfi, Giuseppe; Paulesu, Eraldo
Abstract: Several studies have shown age-related changes in motor imagery (MI) in older adults and the associated compensatory brain activation patterns; most of these studies have used explicit MI tasks or implicit MI tasks focused on mental rotation of body parts. Here, we address the effect of ageing on MI for the more complex visuomotor transformations entailed by mentally simulated hand-tool interactions triggered by a grip selection task (GST) for tools used in daily life. We studied 22 young and 22 elderly subjects performing the GST, in which they were asked to report whether they would grip a portrayed tool with an overhand or an underhand grip. We found a behavioral decline in the elderly group, accompanied by reduced activations of the left posterior parietal lobule, in a subregion associated specifically with reaching behavior by previous investigations. No differences were observed in the temporal cortices associated with object semantics. These results suggested a specific age-related vulnerability of the neural substrates, particularly for the imaginary reaching component of the task, rather than for the semantically driven grasping component. The combination of behavioral deficits and reduced activation of specific brain regions speaks in favor of a specific age-associated deficit for the complex imaginary movements required by the GST.